Enteropathogens associated with enterocoliti in foals: Epidemiological, clinical aspects and diagnostic methods (Research, Society and Development, 2021)
Enterocolitis is among the conditions that most affect foals in horse breeding systems worldwide. It is estimated that up to 80% of foals in the first six months of life are affected by at least one episode of diarrhea, mostly mild and transient episodes, however, the costs of treatment and the mortality rate that this condition can generate are impacting for breeders and owners. The aim of this review is to describe the epidemiological, clinical and diagnostic methods of the main bacterial, viral and parasitic enteropathogens involved in episodes of diarrhea in foals from birth to 8 months of age. Articles available on the Mendeley, MEDLINE, pubMed and SciELO platforms were used. Among the main enteropathogens causing diarrhea in foals, we can highlight infections caused by Salmonella spp., Escherichia coli, Rhodococcus equi, Clostridium perfringens, Clostridium difficile, Lawsonia intracellularis, Rotavirus, Coronavirus and helminths. The identification of high-risk foals and the implementation of therapeutic protocols based on complementary tests and identification of the etiological agent are of great importance for the success in the treatment, control and implementation of prophylaxis methods in the breeding systems.